2015
DOI: 10.1590/0102-311x00000915
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre a cobertura de equipes de saúde bucal na saúde da família e o aumento na produção ambulatorial dos municípios brasileiros, 1999 e 2011

Abstract: Resumo Analisar a associação entre a cobertura populacional de equipes de saúde bucal da Estratégia Saúde da Família (ESF) e a diferença nas taxas de uso de serviços odontológicos públicos nos municípios brasileiros em 1999 e 2011. A amostra contou com 5.507 municípios nos 2 anos. Foram utilizados dados de sistemas de informação oficiais e se procedeu à regressão logística para modelar o incremento nas taxas de procedimentos. Observou-se que 85% dos municípios possuíam equipes de saúde bucal da ESF em 2011 e h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
31

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
1
9
0
31
Order By: Relevance
“…The reduction in the number of OHT among some Brazilian municipalities complements data from previous studies that show that the increase in the number of oral health teams in Brazil positively affects the use and access to dental services 23 , 24 , as well as greater user satisfaction 25 . A study conducted with 12-year-old schoolchildren and adolescents aged 15 to 19 years in Rio Grande do Sul showed that young people covered by the OHT have greater use of dental health services than those not covered 26 .…”
Section: Discussionsupporting
confidence: 74%
“…The reduction in the number of OHT among some Brazilian municipalities complements data from previous studies that show that the increase in the number of oral health teams in Brazil positively affects the use and access to dental services 23 , 24 , as well as greater user satisfaction 25 . A study conducted with 12-year-old schoolchildren and adolescents aged 15 to 19 years in Rio Grande do Sul showed that young people covered by the OHT have greater use of dental health services than those not covered 26 .…”
Section: Discussionsupporting
confidence: 74%
“…Federal resources (nominal funding) for states and municipalities increased from R$ 83.4 million in 2003 to R$ 916 million in 2014, an increase of 10.9 times in the period, however, the use of public dental services remains around 30.7% versus 69.3% of private dental services 5 . Published studies have focused on this policy 7,8 , specifically on the Dental Specialties Centers (CEO) 9-11 , as well as on the results of that implementation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested that the presence of oral health technicians and dental assistants (OHT and DA, respectively) in health teams increases the access of the population and the productivity of professional dental surgeons [11]. In this context, Florianópolis presents 46.99% coverage of OHT with the presence of OHT and DA, leading to understand that the expansion of the oral health care network, with complete OHT teams, will positively impact the curative and preventive measures in the municipality.…”
Section: Discussionmentioning
confidence: 99%